Application of Integrated Pest Management to Build Awareness of Coffee Farmer Behavior - Dwi Indah Rosalina; Sri Tjondro Winarno; Nuriah Yuliati (Dinasti Publisher, 2025)
The agricultural sector, especially coffee cultivation, faces major challenges in managing pests and diseases in a sustainable manner. This study aims to analyze the effect of the implementation of Integrated Pest Management (IPM) on the behavioral awareness of coffee farmers in East Java. Using a quasi-experimental approach and mixed methods, this study involved four farmer groups: Sumber Urip, Mulyo Jaya, Suka Maju, and Kebun Jeruk Sukses. The results showed that the application of IPM significantly increased farmers knowledge and skills, and influenced their awareness of environmentally friendly agricultural practices. The convergent validity test showed that all indicators had significant loading factors, with R² values ranging from 15.1% to 52.1%, which showed that the variation in farmers behavioral awareness could be explained by the implementation of IPM. Supporting factors such as resource availability, farmer awareness, and community support contribute positively, while lack of prior knowledge and limited access are obstacles. Recommendations to improve the effectiveness of IPM implementation include the development of relevant training materials, increased farmer involvement, and stakeholder support. With a comprehensive approach, it is hoped that coffee farmers can become more aware and implement sustainable agricultural practices, supporting the sustainability of the agricultural sector in Indonesia.